Arte, arquitetura e arqueologia no Levante Sul à luz de Ex 31,1-11 - Miranda Filho, Francisco Marques (2022)
The research proposed in this dissertation has as its starting point the new understanding that contemporary archeology has developed about the classification of all art and architecture produced in the Ancient Near East, privileged locus of the biblical narrative. The choice of Ex 31:1-11, is related not only to the fact that it is the story told about the origin of ancient Israel, but mainly to seek, from a re-reading of the pericope, the possibility that the same art and architecture may have been produced by Judaism, even though contemporary exegesis situates the passage in the post-exilic period. This is the reason for beginning to situate the narrative in the Exodus saga as a whole, and correlating it with the other two great descriptive and prescriptive narratives of Ex 25:1-30:38 and 35:4-39:43, which describe the construction of the Desert Sanctuary. The research undertaken considered the exuberance of Mesopotamian art and architecture in comparison with that produced in the Southern Levant, seeking to offer a counterpoint to the artistic periphery attributed by archaeology. The paper not only proposed an analysis of the narrative itself, but investigated the problem of the refusal to produce images that Jewish aniconia established as a theological thesis. The final argument of the paper also briefly looked at the theological understanding that beauty can offer as a foundation on the relationship between art and theology in understanding faith. Theological aesthetics is to say: art speaks of beauty, and the glory of God is the full expression of this sought-after beauty